The Role of Teachers as Motivators and Their Influence on Learning Outcomes (Analysis Study of Class 1D Santri at LPI Mudi Putri Mesjid Raya Samalanga, Bireuen Regency) - Tgk Armis; Muliani; Izzatul Mauliza (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
In the field of education, the teacher is a very important role in teaching and learning, in order to educate humans from stupidity to become intelligent humans, and educate humans from failure to become successful and talented humans. This paper deals with the role of teachers as motivators and their influence on learning outcomes (analysis study of class 1D Santri at LPI Mudi Putri Mesjid Raya Samalanga, Bireuen Regency). The type of research method that researchers use in this study is qualitative methods. This study found that in guarding learning activities, teachers are not just directing various learning materials as has been implemented by the education curriculum section at Dayah MUDI Putri Mesjid Raya Samalanga, Bireuen Regency, but the teacher's job is to always provide motivation in learning objectives, and provide advice that can soften the hearts of students. This study also found that the factors that influence students' learning outcomes both inside and outside the classroom, are not consistent in learning goals.